Improving the luminescence properties and powder morphologies of red-emitting Sr0.8Ca0.19AlSiN3:0.01Eu2+ phosphors for high CRIs white LEDs by adding fluxes. Issue 15 (15th October 2019) - Zhang, Nan; Wang, Zhijun; Zhang, Huacheng; Sun, Yili; Yuan, Tianyu; Tao, Chunjing; Yang, Zhiping; Li, Panlai
Abstract: Red-emitting Sr0.8 Ca0.19 AlSiN3 :0.01Eu 2+ phosphor with halide fluxes for use in the production of white light-emitting diodes (white LEDs) with high-colour rendering indices (CRIs) was prepared through the high-temperature solid-state method. Fluoride (NaF, SrF2, BaF2, CaF2, AlF3 ·3H2 O and CeF3 ), chloride (NH4 Cl, BaCl2, MgCl2, NaCl and LiCl) and composite fluxes (NaF + SrF2, SrF2 +NH4 Cl and NaF + NH4 Cl) were applied in the phosphors. NaF, SrF2, NH4 Cl and NaF + SrF2 fluxes had prominent effects on the characteristics of Sr0.8 Ca0.19 AlSiN3 :0.01Eu 2+ phosphors. Sr0.8 Ca0.19 AlSiN3 :0.01Eu 2+ phosphors with various powder morphologies can be obtained through the addition of fluxes, which are conducive for phosphor formation. The powder morphologies of phosphors incorporated with NaF + SrF2 were preferable to those of powders incorporated with other fluxes. This result indicated that the incorporation of NaF + SrF2 into Sr0.8 Ca0.19 AlSiN3 :0.01Eu 2+ yielded phosphors with high luminescent intensity and quantum efficiency, excellent thermal stability, narrow full widths at half-maximum (FWHM, 75.2 nm), uniform rod-like morphologies with large particle sizes (D50 = 16.99 μm) and good particle dispersion. White LEDs with high CRIs were obtained by combining prepared phosphors (NaF + SrF2 additive) with the commercial green-emitting phosphors Y3 (Al, Ga)5 O12 :Ce 3+ and (Sr, Ba)2 SiO4 :Eu 2+ . White LEDs with Y3 (Al, Ga)5 O12 :Ce 3+ and (Sr, Ba)2 SiO4 :Eu 2+ phosphors had correlated colour temperatures (CCTs) of 3064 and 3023 K, respectively, and CRIs of 81.8 and 92.4, respectively. Therefore, NaF + SrF2 can be used as a favourable flux for the production of Sr0.8 Ca0.19 AlSiN3 :0.01Eu 2+ .